2015
DOI: 10.1002/ece3.1635
|View full text |Cite
|
Sign up to set email alerts
|

Baiting improvesCPUEin nine‐spined stickleback (Pungitius pungitius) minnow trap fishery

Abstract: Whether or not baiting influences stickleback catch per unit effort (CPUE) remains a matter of debate among stickleback researchers: While the opinions about the impact of baiting on CPUE differ, supporting quantitative data are scarce. The effect of baiting and trap type on nine-spined stickleback (Pungitius pungitius) CPUE was studied in a field experiment conducted over four consecutive days in a small pond in northeastern Finland. The results show that baited traps yielded better (mean CPUE = 1.24 fish/tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
5
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 24 publications
1
5
0
Order By: Relevance
“…Individual and other biotic interactions in the wild might influence escape (and entry) probability in a trap model-specific fashion. Nevertheless, whether caused by variation in entry or escape rates, the differences in CPUE among different trap models were clear and consistent with estimates available from earlier studies 15 16 17 18 .…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…Individual and other biotic interactions in the wild might influence escape (and entry) probability in a trap model-specific fashion. Nevertheless, whether caused by variation in entry or escape rates, the differences in CPUE among different trap models were clear and consistent with estimates available from earlier studies 15 16 17 18 .…”
Section: Discussionsupporting
confidence: 89%
“…This is a significant finding, since the performance of metallic and canvas traps has never been directly compared in the stickleback fishery. Several earlier studies have compared the performance of the two canvas trap models, both in three-spined 16 and nine-spined stickleback fisheries 15 17 , and found that the black traps catch more (adult) sticklebacks than the red traps in both species. Hence, the results from earlier studies would encourage the use of black canvas traps over the red ones.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations